2018
DOI: 10.1080/14681811.2018.1530650
|View full text |Cite
|
Sign up to set email alerts
|

Not by CSE alone… Furthering reflections on international cooperation in sex education

Abstract: Recently in Sex Education authors have raised concern with regards to Comprehensive Sexuality Education (CSE) in resourcepoor countries as part of Western European development aid policy. It has been argued that the agency-focused and rightsbased nature of 'northern' sexuality education puts too much responsibility on young people's shoulders and disregards their insecurity and shame, as well as local culture more generally. By promoting a rights-based approach to CSE in countries in the South, European develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“… 48 Attitudes towards sexual minorities and other aspects of sexual and reproductive rights; Attitudes towards sexual consent and sexual violence; Perceived social norms related to sexual identities and preferences. Critical reflection skills Ability to critically assess and challenge norms and messages related to gender and sexuality 1 , 28 , 29 , 49–52 Critical consciousness associated with positive sense of self among a sample of lesbian, gay and bisexual adolescents in Hong Kong; 52 Critical reflection on cultural, religious and societal values and norms related to sexuality is considered a primary learning objective in international standards for sexuality education 29 , 50 Critical consciousness; Critical refection; Critical awareness; Critical action. Coping and stress management skills Ability to deal with and learn from negative experiences adversities, handle stress and pressure related to social and sexual expectations 1 , 28 , 29 , 35 , 53 Lack of readiness to cope with the onset of menstruation linked with negative puberty experiences among low-income girls in the US; 39 Skills for mobilising resources (e.g.…”
Section: A Conceptual Framework For Adolescent Sexual Wellbeingmentioning
confidence: 99%
“… 48 Attitudes towards sexual minorities and other aspects of sexual and reproductive rights; Attitudes towards sexual consent and sexual violence; Perceived social norms related to sexual identities and preferences. Critical reflection skills Ability to critically assess and challenge norms and messages related to gender and sexuality 1 , 28 , 29 , 49–52 Critical consciousness associated with positive sense of self among a sample of lesbian, gay and bisexual adolescents in Hong Kong; 52 Critical reflection on cultural, religious and societal values and norms related to sexuality is considered a primary learning objective in international standards for sexuality education 29 , 50 Critical consciousness; Critical refection; Critical awareness; Critical action. Coping and stress management skills Ability to deal with and learn from negative experiences adversities, handle stress and pressure related to social and sexual expectations 1 , 28 , 29 , 35 , 53 Lack of readiness to cope with the onset of menstruation linked with negative puberty experiences among low-income girls in the US; 39 Skills for mobilising resources (e.g.…”
Section: A Conceptual Framework For Adolescent Sexual Wellbeingmentioning
confidence: 99%
“…It is often argued that information and skills alone are not enough to deal with adolescents' sexual and reproductive health challenges. Policies and programmes must address the socio-economic, cultural and structural dynamics which affect individual risks (Wamoyi et al 2014;Ninsiima et al 2018), or what Svanemyr et al (2015) and Vanwesenbeeck et al (2018) have called a multicomponent approach, calling for an ecological model of analysis. Burns (2002) has indicated that even if girls have the information and skills necessary to have healthy sexual relationships, power imbalances in gender relationships limit their agency to achieve desired goals.…”
Section: Introductionmentioning
confidence: 99%
“…The call for ecological, multicomponent strategies is permeating the SRHR literature nowadays, and the notion that young people's sexual agency and sexual citizenship cannot be achieved by CSE alone is firmly taking hold [46,81]. A 20-year ICPD progress report by Chandra-Mouli et al [58] showed that sexuality education is most impactful when school-based programs are complemented by community elements, including condom distribution, building awareness and support, and increasing demand for SRH education and services among youth.…”
Section: Multicomponent Approachesmentioning
confidence: 99%